The Science Education and History of Ulugh Beg: Astronomer and Mathematician from Samarkand, Uzbekistan - Ruzmetov Mirzabek (Universitas Pendidikan Indonesia (UPI), 2023)
This paper discusses in short about Ulugh Beg, astronomer and mathematician from Samarkand, Uzbekistan. This paper is important for giving education to our generation, especially the Muslim generation that there are Muslim astronomers who are famous and have open minds and knowledge. This paper is expected to advance the spirit of Muslim countries, which at present are still in limited socio-economic conditions so that Muslim countries can rise in the socio-economic and scientific fields.